Leveraging polygenic risk scores to infer causal directions in genotype-by-environment interactions between complex traits - Zinabu Fentaw; Buu Truong; Dovini Jayasinghe; Chris Della Vedova; Gibran Hemani; Beben Benyamin; Elina Hyppönen; S. Hong Lee (Human Genetics, 2026)
Most existing genotype-by-environment interaction (G×E) methods assume a known causal direction as an assumption that often does not hold and can lead to biased estimates and spurious findings. To address this, we introduce the Genetic Causality Inference Model (GCIM), a novel approach designed to infer causal directions in G×E studies. GCIM integrates polygenic risk scores (PRS) for both the exposure and the outcome to strengthen causal inference and reduce spurious interaction signals. We evaluated GCIM using simulated data across varying genetic and residual correlation settings and compared its performance to existing PRS-by-environment (PRS×E) models under both null and alternative G×E scenarios. GCIM was also applied to real-world UK Biobank data in both causal directions. GCIM consistently outperformed existing methods by accurately identifying the absence of G×E variance and avoiding false positives, even in the presence of strong phenotypic heteroscedasticity due to residual heterogeneity. Other methods often generated spurious associations, especially under reverse causality. Applying GCIM to UK Biobank data, we investigated 11 circulating biomarkers (including liver enzymes, lipids, and inflammatory markers) and three anthropometric traits (BMI, body fat, and waist-to-hip ratio [WHR]). GCIM identified that bilirubin modulates genetic effects on BMI and WHR, while body fat modulates genetic effects on C-reactive protein, with associations remaining significant after multiple testing corrections. Overall, GCIM provides a more reliable framework for GxE analysis, particularly under challenging conditions such as residual heterogeneity and uncertain causal direction. However, further development is needed to improve its statistical power.

Plankton assemblages across a coastal to oceanic gradient of Northern Australia and responses to a storm perturbation in the Argo Basin - Claire H. Davies; Ruth S. Eriksen; Sahan Jayasinghe; Felicity McEnnulty; Michael R. Landry (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

α-Glucosidase inhibitors from an endophytic fungus Edenia gomezpompae from Costus speciosus - B. M. S. Nilmini; Kavindya Samarakoon; Deepthi Yakandawala; Savitri Kumar; Nimal Adikaram; Lalith Jayasinghe; Hiroshi Araya; Yoshinori Fujimoto (Vegetos, 2025)

Advancements and limitations in polygenic risk score methods for genomic prediction: a scoping review - Dovini Jayasinghe; Setegn Eshetie; Kerri Beckmann; Beben Benyamin; S. Hong Lee (Human Genetics, 2024)

Innovative digital twin with artificial neural networks for real-time monitoring of structural response: A port structure case study - S.C. Jayasinghe; M. Mahmoodian; A. Sidiq; T.M. Nanayakkara; A. Alavi; Sam Mazaheri; F. Shahrivar; Z. Sun; S. Setunge (Ocean Engineering, 2024)

Experimental study of mechanistic factors influencing solvent-driven fractional crystallization of calcium sulfate - Ashini S. Jayasinghe; Caleb Stetson; Christopher J. Orme; Meng Shi; Aaron D. Wilson (Desalination, 2024)

Effects of street tree configuration and placement on roadside thermal environment within a tropical urban canyon - Sachini Jayasinghe; Varuni Jayasooriya; S.M. Dassanayake; S. Muthukumaran (International Journal of Biometeorology, 2024)

Some warning signs detected in coastal pelagic fisheries of the west coast of Sri Lanka: Declining trend of Amblygaster sirm suggesting the need for immediate management initiatives - K. H. K. Bandaranayake; S. S. Gunasekara; S. S. K. Haputhantri; R. P. P. K. Jayasinghe (Sri Lanka Journal of Aquatic Sciences, 2024)
Coastal fisheries, mainly characterized by small pelagic species, are significant on the west coast of Sri Lanka in terms of livelihood and food security. However, currently, the fishery has faced numerous challenges, particularly with the stock depletion allied with poor management practices. The present study was carried out using the time series data of 2001–2020 on the west coast of Sri Lanka representing four fisheries districts - Kalutara, Colombo, Negombo, and Chilaw - to explore the present status and the tendency of the fishery towards management considerations. The analysis was based on the outboard engine fiber-reinforced plastic boats (OFRP) with small meshed gillnets, which are the main boat gear combination that exists in the fishery. The recent five-year landings within the study period indicated that the highest average catch rates resulted in the onset of the southwest monsoon and extended until the end of the northeast monsoon. The catch rates of fishery exhibited greater inter-annual fluctuations during a two-decade period, with an average of 66.7 ± 17.3 kg per trip from 2011 to 2020. Over the past two decades, the Mean Trophic Level (MTL) of the coastal fish landings ranged from 3.13 to 3.62 and showed a declining trend with the forecast of 3.38 for 2022-2026. Moreover, the catch rates and the relative contribution of Amblygaster sirm, one of the main target species in the country, showed a declining trend over the past two decades while indicating the need for immediate management initiatives.

Dryspells and Minimum Air Temperatures Influence Rice Yields and their Forecast Uncertainties in Rainfed Systems - Abhijeet Abhishek; Mantha S. Phanikumar; Alicia Sendrowski; Konstantinos M. Andreadis; Mahya G.Z. Hashemi; Susantha Jayasinghe; P.V. Vara Prasad; Roberts J. Brent; Narendra N. Das (Agricultural and Forest Meteorology, 2023)

Present Status and Future Developmental Perspectives of Pole and Line Fishery in Sri Lanka - K. H. K. Bandaranayake; S. S. Gunasekera; R. P. Prabath K. Jayasinghe; Rekha Maldeniya (Sri Lanka Journal of Aquatic Sciences, 2023)
Pole and line fishery is one of the oldest traditional techniques employed in tuna fishing in the Indian Ocean including Sri Lanka, which is mainly targeted to exploit skipjack tuna. This fishery has fallen to a relatively low level of significance during the past three decades. The potentialities for the expansion of pole and line fishery in Sri Lanka are regained with the possible negative consequences allied with the drift gill net in the region. The present study attempts to understand the factors that hinder the practice of gear progressively in past decades while providing necessary recommendations for the future expansion of the fishery. Scarcity of Dipterygonotus balteatus (Redbait), the main live bait species used in the fishery is one of the main reasons documented in the literature. The present findings based on Dr Fridtjof Nansen survey in 2018 revealed that the resource is abundant in the waters but requires an efficient harvesting technique. The impediment factor which hindered the popularization of the fishery is the deficiency of free schools of skipjack tuna where more than 99% of the surface tuna were found to be concentrated beyond the fishing range of existing practices. The commercialization of pole and line fishery in Sri Lanka will be feasible primarily with the modernization of the fishery which includes vessel upgrades, introduction of Fish Aggregating Devices (FADs), forecasting of free tuna schools, and efficient methods to harvest live bait and secondarily through proper awareness and skill development.

Feasible techniques for valorisation of construction and demolition waste for concreting applications - H. M. S. C. H. Bandara; G. Thushanth; H. M. C. C. Somarathna; D. H. G. A. E. Jayasinghe; S. N. Raman (International Journal of Environmental Science and Technology, 2023)

Distribution and Abundance of the Blue Whale (Balaenoptera musculus indica) off Sri Lanka during the Southwest Monsoon 2018 - Liyanage U. S. P. Kirumbara; Jayasinghe R. P. P. Krishantha; Krakstad Jens-Otto; Arulananthan Kanapathipillai (Journal of Marine Science and Engineering, 2022)
Blue whales Balaenoptera musculus are the most abundant and widely distributed cetacean species in Sri Lankan waters. A vessel-based opportunistic line transect survey focusing on marine mammals was conducted in Sri Lankan waters between 24 June to 12 July 2018, while an ecosystem survey was performed by the R/V Dr. Fridtjof Nansen. The entire transect length was 2090 km within an area of 3895 km2. Overall, 72% (n = 57) of blue whale observations were group assemblages ranging between 1 and 5 individuals out of a total of 79 sightings. The largest aggregations of blue whales were recorded at the intersection of the submarine canyon off the coastline of Mirissa and busy shipping lanes between Dondra Head and Galle, where previous ship strikes were recorded. Overall, the average observed group size was 2.64 (CV, 12.34%; 95% CI, 2.07–3.38), the average group density was 0.0029 km−2 (CV, 35.96%; 95% CI, 0.00145–0.00610), and the total blue whale abundance within the survey area was 513 individuals (CV, 38.02%; 95% CI, 243–1083). These survey results fill vital knowledge gaps regarding the abundance and distribution of blue whales in Sri Lanka, which is essential for the establishment of management and conservation strategies.

Evolution of adverse drug reactions reporting systems: paper based to software based - M. T. Madhushika; T. P. Weerarathna; P. L. G. C. Liyanage; S. S. Jayasinghe (European Journal of Clinical Pharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Identification of thermal hotspots through heat index determination and urban heat island mitigation using ENVImet numerical micro climate model - T. A. N. T. Perera; T. M. D. Nayanajith; G. Y. Jayasinghe; H. D. S. Premasiri (Modeling Earth Systems and Environment, 2022)

Development of design guideline for the baseplate thickness of lattice towers - A. M. L. N. Gunathilaka; C. S. Lewangamage; M. T. R. Jayasinghe (Innovative Infrastructure Solutions, 2021)

Colletotrichum species causing anthracnose disease in A. andraeanum, manifested as spathe rot also in addition to spadix rot and leaf spot. - I. S. Komala Vithanage; D. M. D. Yakandawala; S. S. N. Maharachchikumbura; L. Jayasinghe; N. K. B. Adikaram (European Journal of Plant Pathology, 2021)

Pharmaceutical and Personal Care Products (PPCPs) in the environment: Plant uptake, translocation, bioaccumulation, and human health risks - S. Keerthanan; Chamila Jayasinghe; Jayanta Kumar Biswas; Meththika Vithanage (Critical Reviews in Environmental Science and Technology, 2021)

Effects of Rht-B1 and Ppd-D1 loci on pollinator traits in wheat - Takashi Okada; J. E. A. Ridma M. Jayasinghe; Paul Eckermann; Nathan S. Watson-Haigh; Patricia Warner; Yonina Hendrikse; Mathieu Baes; Elise J. Tucker; Hamid Laga; Kenji Kato; Marc Albertsen; Petra Wolters; et al. (Theoretical and Applied Genetics, 2019)

Mercury and cadmium in swordfish and yellowfin tuna and health risk assessment for Sri Lankan consumers - B. K. K. K. Jinadasa; G. S. Chathurika; C. D. Jayaweera; G. D. T. M. Jayasinghe (Food Additives & Contaminants Part B-Surveillance, 2019)

Opposite fates of the purine metabolite allantoin under water and nitrogen limitations in bread wheat - Alberto Casartelli; Vanessa J. Melino; Ute Baumann; Matteo Riboni; Radoslaw Suchecki; Nirupama S. Jayasinghe; Himasha Mendis; Mutsumi Watanabe; Alexander Erban; Ellen Zuther; Rainer Hoefgen; Ute Roessner; et al. (Plant Molecular Biology, 2019)

Cattle and water buffalo densities wading into small village reservoirs of Sri Lanka impact on yields on the culture-based fisheries thereof - Asanka D. Jayasinghe; J. Arachchige Athula; Sena S. De Silva; Upali S. Amarasinghe (Sri Lanka Journal of Aquatic Sciences, 2018)
This study investigated whether allochthonous inputs generated by cattle and water buffaloes grazing in the catchment or wading in the water in small village reservoirs of Sri Lanka can make a significant effect on yields from culture-based fisheries of those reservoirs. The analysis is based on limnological data of 37 randomly selected reservoirs. As culture-based fish yield data were available over the 2002 - 2003 period only for 23 reservoirs, fish yield data from seven more reservoirs were gleaned for the present analysis. Cattle and water buffalo densities (BD) in 37 reservoirs where limnological data were available, were found to be significantly correlated to the biological productivity-related parameters such as chlorophyll-a content. Culture-based fish yield in the 30 reservoirs varied from 54.6 to 1800.8 kg ha-1 and BD associated with the reservoirs studied varied from 0.90 number ha-1 to 216.25 numbers ha-1. Fish yield (FY) was significantly correlated with BD the relationship being, FY = 4.758 BD + 242.740 (R2 = 0.345; p

Conversion between solid and beam element solutions of finite element method based on meta-modeling theory: development and application to a ramp tunnel structure - J. A. S. C. Jayasinghe; M. Hori; M. R. Riaz; M. L. L. Wijerathne; T. Ichimura (Earthquake Engineering and Engineering Vibration, 2017)

Multi-mesh gillnet selectivity of Oreochromis mossambicus and O. niloticus (Cichlidae) in the fishery of three large perennial reservoirs in Sri Lanka - R. P. Prabath K. Jayasinghe; Upali S. Amarasinghe; Jacques Moreau (Sri Lanka Journal of Aquatic Sciences, 2017)
As in many tropical reservoir fisheries, the major fishing gear in the reservoirs of Sri Lanka is gillnet. Gillnets of a wide range of stretched mesh sizes (6.9 - 11.4 cm) are used in individual boats in Sri Lankan reservoirs targeting mainly two exotic cichlid species, Oreochromis mossambicus and O. niloticus, which dominate the fisheries accounting for over 80% of the landings. Although the filament characteristics and dimensions of gillnets of different mesh sizes are uniform, their mesh composition varies from boat to boat making catch samples in individual boats are under the influence of different selectivity patterns. As such, an approach is presented for constructing the overall selection curves in the sampled boats during different sampling occasions for the two cichlid fish species in the three reservoirs. For this purpose, gillnet selectivity of each mesh size was determined using Baranov-Holt method. Probabilities of capture of mesh-wise gillnet selection curves were then summed up giving weight to the contribution of each mesh size to the total number of net pieces in the sampled boat, to determine the overall gillnet selection from gillnets of all mesh sizes. The importance of the findings of the present study for length-based stock assessment methods and for imposing mesh regulations to the gillnet fisheries in reservoirs of Sri Lanka is discussed.

Herklotsichthys quadrimaculatus Korumburuwa in the stilt fishery in Southern Sri Lanka: Are they really poisonous? - K.H.M. Ashoka Deepananda; Upali S. Amarasinghe; Udith K. Jayasinghe Mudalige (Sri Lanka Journal of Aquatic Sciences, 2016)
Stilt fishing is a unique fish catching method confined only to southern coast of Sri Lanka from Galle to Matara. Stilt fishermen sitting on a cross bar called “Petta” tied to vertical pole planted in the reef and carrying out rod and line fishing are a Sri Lankan icon that attracts local and foreign tourists’ attention. This small-scale, seasonal fishing method has a long history and fishers use traditional ecological knowledge for their fishing activities (Deepananda et al. 2016). Two fish species, big eye scad (Selar crumenophthamus) locally known as Esgedi bolla and bluestripe herring (Herklotsichthys quadrimaculatus) locally known as Korumburuwa are caught by this fishing method. Of the two species, Korumburuwa is fished throughout the fishing season which commences from early June with the onset of southwest monsoon and continues until February/March of the following year. Due to freshness of the fish that can be bought at affordable price, most buyers prefer purchasing Korumburuwa at the place they are fished traditionally called as Rendapola. However, there is a traditional belief among some consumers that eating Korumburuwa causes some toxic effect leading to vomiting, dizziness and sometimes fainting among those who consume this species, and also deaths of domestic animals such as cats. These beliefs have detrimental impacts on the marketing of H. quadrimaculatus caught in stilt fishing. Such widespread beliefs may have been propagated rapidly among consumers through electronic mass media. For instance, recent media reports on fish poisoning by Auxis thazard in Muttur and observation of bioluminescence in Decapterus ruselli in Weligama seriously impacted consumption of fish by general public. This communication reports the findings of a short-term study on gut contents of H. quadrimaculatus, which was carried out to investigate the root cause of the people’s beliefs that Korumburuwa is poisonous.

A new begomovirus–betasatellite complex is associated with chilli leaf curl disease in Sri Lanka - D. M. J. B. Senanayake; J. E. A. R. M. Jayasinghe; S. Shilpi; S. K. Wasala; Bikash Mandal (Virus Genes, 2013)

Screening of fungicides against Corynespora leaf fall disease of rubber under nursery conditions - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; D. Siriwardana (Journal of Plant Diseases and Protection, 2010)

Evaluation of screening methods against Corynespora leaf fall disease of rubber (Hevea brasiliensis) - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; W. P. K. Silva; E. A. D. N. Nishantha (Journal of Plant Diseases and Protection, 2010)

Variability of Hevea isolates of Corynespora cassiicola from Sri Lanka - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; D. Siriwardana (Journal of Plant Diseases and Protection, 2009)

Determining Tissue-Lead Levels in Large Game Mammals Harvested with Lead Bullets: Human Health Concerns - L. J. S. Tsuji; B. C. Wainman; R. K. Jayasinghe; E. P. VanSpronsen; E. N. Liberda (Bulletin of Environmental Contamination and Toxicology, 2009)

Lead Pellet Ingestion and Liver-Lead Concentrations in Upland Game Birds from Southern Ontario, Canada - N. Kreager; B. C. Wainman; R. K. Jayasinghe; L. J. S. Tsuji (Archives of Environmental Contamination and Toxicology, 2008)

Dihydrochalcones with radical scavenging properties from the leaves of Syzygium jambos - U. L. B. Jayasinghe; R. M. S. Ratnayake; M. M. W. S. Medawala; Y. Fujimoto (Natural Product Research, 2007)

Culture‐based fisheries in non‐perennial reservoirs of Sri Lanka: influence of reservoir morphometry and stocking density on yield - U. A. D. JAYASINGHE; U. S. AMARASINGHE; S. S. DE SILVA (Fisheries Management and Ecology, 2006)
Culture‐based fish yield in non‐perennial reservoirs of Sri Lanka was related to reservoir morphometry and stocking density. The reservoirs were stocked mainly with fingerlings of one Chinese and three Indian major carp species, common carp, Cyprinus carpio L., and the genetically improved farmed tilapia strain of Nile tilapia, Oreochromis niloticus (L.), at four pre‐determined species combinations and a range of stocking densities [ SD (fingerlings ha −1 )]. Twenty‐three reservoirs were harvested successfully at the end of the culture period of 2002–2003. Basic limnological and morphometric parameters, including shoreline development ( D L ) and shoreline area ratio ( R LA ), were estimated for each of the 23 reservoirs. Bray–Curtis similarity and non‐metric multidimensional scaling using mean values of limnological data revealed that reservoirs could be ordinated into two major clusters, one with intact sample distribution due to similar trophic characteristics and the other with scattered sample distribution. Reservoirs in the cluster with similar trophic characteristics showed significant correlation ( P R LA and total fish yield ( Y ). A multiple regression equation, Y = −693 + 4810 R LA + 0.484 SD , was generated to estimate fish harvest in relation to SD .

Culture‐based fisheries in non‐perennial reservoirs in Sri Lanka: production and relative performance of stocked species - W. M. H. K. WIJENAYAKE; U. A. D. JAYASINGHE; U. S. AMARASINGHE; J. A. ATHULA; K. B. C. PUSHPALATHA; S. S. DE SILVA (Fisheries Management and Ecology, 2005)
In Sri Lanka, there is a great potential for the development of culture‐based fisheries because of the availability of around 12 000 non‐perennial reservoirs in the dry zone ( Catla catla Hamilton and rohu Labeo rohita Hamilton) and Chinese (bighead carp Aristichthys nobilis Richardson) major carps, common carp Cyprinus carpio L., genetically improved farmed tilapia (GIFT) strain of Nile tilapia, Oreochromis niloticus (L.) and post‐larvae of giant freshwater prawn, Macrobrachium rosenbergii De Man, at three different species combinations and overall stocking densities (SD) ranging from 218 to 3902 fingerlings ha −1 , during the 2002–2003 culture cycle. Of the 32 reservoirs stocked, reliable data on harvest were obtained from 25 reservoirs. Fish yield ranged from 53 to 1801 kg ha −1 and the yields of non‐perennial reservoirs in southern region were significantly ( P P P a and fish yield exhibited a positive second order relationship ( P P O. niloticus had the lowest specific growth rate among stocked species and freshwater prawn had a low return.

Soil and Plant Lead of Upland Habitat Used Extensively for Recreational Shooting and Game Bird Hunting in Southern Ontario, Canada - J. Holdner; B. Wainman; R. Jayasinghe; E. Van Spronsen; J. D. Karagatzides; E. Nieboer; L. J. S. Tsuji (Bulletin of Environmental Contamination and Toxicology, 2004)

Tissue?Bismuth Levels of Game Birds Harvested with Bismuth Shotshell: Policy Implications - L. J. S. Tsuji; B. C. Wainman; R. K. Jayasinghe; J. D. Karagatzides; E. Van Spronsen; E. Nieboer (Bulletin of Environmental Contamination and Toxicology, 2004)